Gated recurrent deep learning approaches to revolutionizing English language learning for personalized instruction and effective instruction - Bo Sun (Scientific Reports)
Abstract Communication is essential for success in today’s world, making English language learning (ELL) a crucial skill. Innovative solutions are required to tackle complex language learning issues and meet the various demands of learners. Personalized learning successfully considers students’ unique interests, strengths, and weaknesses. The study investigates the revolutionary possibilities of Gated Recurrent Neural Networks (GRNN) to improve ELL-tailored training. The GRNN-ELL model dynamically adapts to the learner’s progress using powerful sequence modelling and language processing algorithms. The training and evaluation architecture and dataset are detailed with an emphasis on optimization techniques. According to the experimental data, fluency, vocabulary diversity, contextual relevance, and engagement levels are four areas where GRNN-ELL outperforms conventional measurements. With the provision of personalized learning experiences, the promotion of intercultural communication skills, and the resolution of educational demands worldwide, the results highlight the possibility of GRNN-ELL revolutionizing ELL. The study stresses the significance of individualized training in effectively acquiring a language in today’s worldwide environment.